TANTANGAN PENDIDIKAN DASAR DI MASA DEPAN : INTEGRASI TEKNOLOGI, KURIKULUM ADAPTIF, DAN PERAN GURU DALAM ERA GLOBAL - Ananda , Rizki; Andini, Paramitha; fitri, Rindu Iladini; Rahmadani, Anjli; Dwi Meilani, Ajeng (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In the era of rapid global change, the integration of technology, adaptive curriculum, and the evolving role of teachers are critical to shaping the future of primary education. This research aimed to explore the convergence of these elements to improve educational outcomes in elementary schools. Through a literature review methodology, the study analyzed relevant academic journals, policy reports, and educational frameworks over the last decade. The findings highlight the significant impact of technology in instructional design and student interaction, especially with the use of gamification and augmented reality tools. The study also examined the challenges and opportunities presented by adaptive curriculum models, demonstrating their effectiveness in catering to diverse student needs. Furthermore, the research emphasizes the need for redefining the role of teachers as facilitators and leaders in the learning process, particularly in a digital environment. The research concludes with conceptual recommendations for an integrative model of education that combines technology, flexible curricula, and teacher leadership to address the challenges faced by primary education today. The results suggest that policy changes should focus on enhancing teacher professional development and improving infrastructure to support digital learning